Hydrogenation of chlorate ions by commercial carbon supported palladium catalysts—a comparative study - Sikora Emőke; Karacs Gábor; Kocserha István; Muránszky Gábor; Fiser Béla; Bela Fiser; Фішер Бейло; Viskolcz Béla; Vanyorek László (Akadémiai Kiadó, 2020)
Abstract. The chlorate elimination potential of three commercial activated carbon supported 10 wt% palladium catalysts (Cat-I, Cat-II and Cat-III) have been compared in heterogeneous catalytic hydrogenation. The physical–chemical properties of the catalysts were characterized by using high-resolution transmission electron microscopy, X-ray difractometry, Fourier-transform infrared spectroscopy and ζ potential measurements. Chlorate reduction tests have been carried out by applying the same procedure and conditions in each case. The studied catalysts were active, but Cat-I and Cat-III showed higher activity, and eliminated 93% and 91% of chlorate, respectively. Reuse tests have also been carried out to compare the catalysts. Although Cat-I and Cat-III were shown almost equally high activity in the frst cycle, the reuse tests showed that Cat-III could have a better applicability.
Editorial board: https://link.springer.com/journal/11144/editorial-board
Contents: https://link.springer.com/journal/11144/volumes-and-issues/131-1
Keywords: Catalytic hydrogenation; Chlorate elimination; Activated carbon; Pd catalyst